Dampak Pernikahan Dini Terhadap Remaja Ditinjau Dari Kehamilan Pada Siswa SMAN 11 Kota Yogyakarta - Fitria Melina (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: In Southeast Asia about 10 million children under the age of 18 have been married, while in Africa it is estimated that 42% were married before they were 18 years old. Indonesia experienced an increase in the number of early marriages, namely 34,000 applications for early marriage dispensation who were less than 19 years old, 97% approved. Based on data from the Ministry of Religion, 2020 the incidence of early marriage in the city of Yogyakarta is 14 cases, and the highest incidence is in the jetis perspective, amounting to 4 people, so the Indonesian government requires children to study for 12 years. Objective: To determine the impact of early marriage on adolescents in terms of pregnancy in students of SMA N 11 Yogyakarta City. Methods: quantitative descriptive research. The population of all students of SMAN 11 Yogyakarta is 972 people. Simple random sampling technique. The sample size is 90 respondents. Questionnaire instruments. Univariate data analysis. Results: The results of the analysis showed that the level of knowledge of adolescents about the impact of early marriage had knowledge in the sufficient category (60%), the impact of early marriage on pregnancy was in the sufficient category (35.6%). The conclusion is that it is known that the level of knowledge of adolescents about the impact of early marriage in terms of pregnancy at SMANi 11 Yogyakarta City is in the sufficient category.